Anthem for doomed youth - Dunn, Carola (Thorndike, Me. : Center Point Pub., 2011)
In the spring of 1926, the corpses of three men are found in shallow graves off the beaten path in Epping Forest ouside of London. Called in to lead the investigation, DCI Alec Fletcher of Scotland Yard is under urgent orders from his supervisor at the Yark to accomplish two things: solve the mystery quickly, and keep his wife, the Honorable Daisy Dalrymple Fletcher far away from the case.
100093
Keywords: Dalrymple, Daisy (Fictitious character); Police spouses; Murder -- Investigation; Nineteen twenties; Large type books; England; Mystery fiction